Clinical Profile of Patients with Chronic Obstructive Pulmonary Disease - Bari, Md Abdul; Shamsi, Shanjida; Hasan, Mahmud Javed; Ahmed, Sultan (Community Based Medical Journal, 2025)
Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality worldwide, with varying clinical presentations. In Bangladesh, the burden of COPD is rising due to factors such as air pollution, tobacco use, and limited healthcare access. Understanding its clinical profile is essential for tailored management. This study aimed to describe the clinical profile of chronic obstructive pulmonary disease patients. This study was conducted from August 2023 to February 2023 at Community Based Medical College, Bangladesh. Purposive sampling was used to enroll 87 COPD patients diagnosed based on spirometry and clinical criteria. Data on demographics, symptoms, comorbidities, smoking history, and disease severity were collected using structured questionnaires. MS Office tools (Excel, Word) were used for data analysis, including descriptive statistics (mean, percentages). The study revealed COPD patients (mean age 62.4±9.1 years) presented predominantly with dyspnea (92%), chronic cough (85%), and frequent comorbidities (hypertension 36%, diabetes 24%). Most cases were moderate-to-severe (GOLD II-III: 78%), with significant smoking (68%) and biomass exposure (41%), highlighting critical intervention needs in this population. This study highlights the high burden of moderate-to-severe COPD among Bangladeshi adults, with significant smoking and biomass exposure. Findings underscore the urgent need for early detection programs, smoke-free policies, and integrated management of COPD and comorbidities in resource-limited settings. CBMJ 2025 July: vol. 14 no. 02 P:98-104